2013
DOI: 10.1673/031.013.8901
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Some Scorpions,Hemiscorpius lepturusandAndroctonus crassicauda, in a Scorpionism Focus in Ramhormorz, Southwestern Iran

Abstract: Scorpion stings are a common and important health problem in Iran, particularly in south and southwestern Iran, including the province of Khuzestan. In the area of Khuzestan near the city of Ramhormoz, Hemiscorpius lepturus (Scorpionida: Hemiscorpioiidae) and Androctonus crassicauda (Buthidae) are present. Ramhormoz is in southwestern Iran and is one of the most important foci of the scorpion sting problem. The current study was carried out to gain both epidemiological and medical information about scorpion st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
1
28
2
Order By: Relevance
“…This rate is accordance with the results of Vazirianzadeh et al (2008) [23] for Khuzestan and Pour rezaee et al (2010) [24] for Ramshir (in the south east of Khuzestan). Our results are not in accordance with the results in Saudi Arabia [25][26] and Ramhormoz (in the east of Khuzestan) who reported that scorpion stings were greater in the males than in the females [27]. However, our results is not consistent with the results of in Kashan (central of Iran); that they reported that the percentages the epidemiology of scorpion sting is related to the sex of the victims.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This rate is accordance with the results of Vazirianzadeh et al (2008) [23] for Khuzestan and Pour rezaee et al (2010) [24] for Ramshir (in the south east of Khuzestan). Our results are not in accordance with the results in Saudi Arabia [25][26] and Ramhormoz (in the east of Khuzestan) who reported that scorpion stings were greater in the males than in the females [27]. However, our results is not consistent with the results of in Kashan (central of Iran); that they reported that the percentages the epidemiology of scorpion sting is related to the sex of the victims.…”
Section: Discussioncontrasting
confidence: 99%
“…It varies according to the year and location of different studies [28]. However, it may take cultural factors like different activities among females and males [27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be justified due to environmental issues, scorpion types, activity and occupation of people (21,22). The color of the scorpion in most reported cases was yellow (14,16) which is consistent with our findings. According to conducted studies as well as the results obtained in our research, most of the people who were stung were young.…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Cesaretli et al on 930 patients with scorpion stings in Turkey, it was identified that the frequency of the age group 20-29 years old was higher among patients and 33% of patients were treated with anti-venom (15). In a study conducted by Mohseni et al in southwestern Iran, Rāmhormoz, 179 patients with scorpion stings were examined where females had the highest frequency among patients, extremities were the most anatomic place of the stings and the frequency of stings was higher in May to August (16). (19).…”
Section: Discussionmentioning
confidence: 99%
“…The A. crassicauda scorpion (great black scorpion; belonging to family Buthidae) is widely distributed in Iran and neighboring countries (Mohseni et al, 2013;Al-Asmari et al, 2013). Studies have shown that most of stings by scorpions in southwest Iran were attributable to this species (Dehghani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%